2015
DOI: 10.7287/peerj.preprints.904v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perilipin-related protein regulates lipid metabolism in C. elegans

Abstract: The perilipins are lipid droplet surface proteins that contribute to fat metabolism by controlling the access of lipids to lipolytic enzymes. Perilipins have been identified in organisms as diverse as metazoa, fungi, and amoebas but strikingly not in nematodes. Here we identify the protein encoded by the W01A8.1 gene in Caenorhabditis elegans as the closest homologue of metazoan perilipin. We demonstrate that nematode W01A8.1 is a cytoplasmic protein residing on lipid droplets. Human perilipins 1 and 2 localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
6
11
1
Order By: Relevance
“…elegans. We have identified C. elegans locus W01A8.1 (previously annotated as mdt-28) as the sole PLIN gene orthologue in this nematode, henceforth labeled plin-1 (Chughtai et al 2015). Concurrently with our work, other groups have also independently identified this locus as a major LD protein influencing lipid metabolism (Na et al, 2015;Vrablik et al, 2015).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…elegans. We have identified C. elegans locus W01A8.1 (previously annotated as mdt-28) as the sole PLIN gene orthologue in this nematode, henceforth labeled plin-1 (Chughtai et al 2015). Concurrently with our work, other groups have also independently identified this locus as a major LD protein influencing lipid metabolism (Na et al, 2015;Vrablik et al, 2015).…”
Section: Introductionsupporting
confidence: 62%
“…. The strain KV1 [plin-1 -/-] was prepared previously by Cas9/CRISPR-induced gene deletion (Chughtai et al 2015).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The wide expression pattern of F28F8.5 is also keeping with the data Based on the closest sequence similarity of F28F8.5 to MED28 that can be detected informatically in nematode genomes, conserved dual nuclear and cytoplasmic expression and involvement in a wide range of developmental processes, F28F8.5 is named (with WormBase approval) as MDT-28. W01A8.1, which was originally denominated also MDT-28 is renamed as PLIN-1 (Chughtai et al 2015). MED28 is a candidate Mediator complex subunit linking cytoplasmic structural signals towards the core of transcription regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although conserved between insects and mammals, a bona fide MED28 homologue had yet to be identified in nematodes. Our previous work showed that the protein previously identified as " in nematode and other databases is instead the nematode homologue of perilipin, a protein regulating lipid metabolism at the level of lipid droplets and is not related to MED28 (Chughtai et al 2015). Thinking it was unlikely that a MED28 homologue would be absent in nematode genomes, we searched for it using conserved features of MED28 orthologues from various phyla.…”
Section: Introductionmentioning
confidence: 99%